The development of binderless, smokeless briquettes from bituminous colliery waste - England, Trevor (My University, 1993)
Superfines of less than 200 micron are generated when mining coal. They have not been successfully beneficiated in the past and are not acceptable to the consumer. A processh as been developed whereby the superfines are beneficiated, briquetted without the use of binders and devolatilised to produce a premium smokeless briquette which will attract a premium price in the export market. [Abbreviated abstract. Open document to view full version]
A project report submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Science in Engineering Johannesburg, 1993
Keywords: Briquets (Fuel); Coal mines and mining--Waste disposal